COMMUNICATION OF PHYSICAL EDUCATION TEACHER IN PARTNERSHIP WITH STUDENTS OF THE NEW UKRAINIAN SCHOOL (Physical Culture and Sport: Scientific Perspective, 2025)
The article is devoted to the study of the peculiarities of communication of the teacher of physical culture in the conditions of the New Ukrainian School (NUS). The key aspects of the pedagogical partnership between the teacher and the students are considered, effective methods and techniques of communication aimed at creating a positive and motivating learning environment are analyzed. The basic principles of effective interaction are defined, including a dialogical approach, motivational support, feedback and taking into account the individual characteristics of students. Particular attention is paid to the role of communication in the formation of students' values of a healthy lifestyle, the development of their physical abilities and emotional intelligence. Modern methods of communication are outlined that contribute to the formation of a positive microclimate in physical education lessons, the development of social skills and to involve students in an active lifestyle. The basic principles of effective communication, including dialogical approach, empathy, motivational support and use of feedback, are considered. Attention is emphasized on the use of digital technologies to improve the efficiency of the learning process and create the conditions for comfortable work. An important aspect is also the use of modern technologies in communication with students, such as social networks and online platforms. The influence of qualitative communication on the formation of a positive microclimate, the involvement of students in physical education is determined. We argue that in the context of NUSH, a physical education teacher should play the role of not only a trainer but also a mentor who promotes the development of the student's personality.
Keywords: communication; physical education teacher; New Ukrainian school (NUSH); pedagogical partnership; students; healthy lifestyle; educational environment; emotional intelligence; methods of communication; physical development